2017
DOI: 10.1038/s41598-017-16898-x
|View full text |Cite
|
Sign up to set email alerts
|

Raman-Deuterium Isotope Probing for in-situ identification of antimicrobial resistant bacteria in Thames River

Abstract: The emergence and widespread distribution of antimicrobial resistant (AMR) bacteria has led to an increasing concern with respect to potential environmental and public health risks. Culture-independent and rapid identification of AMR bacteria in-situ in complex environments is important in understanding the role of viable but non-culturable and antibiotic persistent bacteria and in revealing potential pathogens without waiting for colony formation. In this study, a culture-independent and non-destructive pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
80
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 53 publications
(59 reference statements)
1
80
0
Order By: Relevance
“…It has been demonstrated that Raman micro-spectroscopy - deuterium isotope probing (Raman-DIP) can identify metabolically active cells by adding a certain percentage of heavy water (D 2 O) in a medium (36, 37). If cells are metabolically active in the presence of D 2 O, a C-D Raman band (2070 – 2300 cm -1 ) forms via NADPD+ ((H/D free exchange) electon transport chain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that Raman micro-spectroscopy - deuterium isotope probing (Raman-DIP) can identify metabolically active cells by adding a certain percentage of heavy water (D 2 O) in a medium (36, 37). If cells are metabolically active in the presence of D 2 O, a C-D Raman band (2070 – 2300 cm -1 ) forms via NADPD+ ((H/D free exchange) electon transport chain.…”
Section: Resultsmentioning
confidence: 99%
“…If cells are metabolically active in the presence of D 2 O, a C-D Raman band (2070 – 2300 cm -1 ) forms via NADPD+ ((H/D free exchange) electon transport chain. As this approach has been demonstrated to be more sensitive compared to tranditional growth curve comparisons, we applied Raman-DIP to explore the activity of the biosensor in response to different carbon sources and thereby the activation pathway (36, 37). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…E, Raman mean spectra of ampicillin resistant strain E coli WH1274, characterized by the emergence of the C D signal in presence of different ampicillin concentrations. Reproduced from Song et al [58] with permission of Springer Nature antibiotic resistance assays. Comprehensive investigations of the "nongrowing but metabolically active" status will promote recognition of treatment deficiencies as well as the development of more effective approaches to overcome the risks of antimicrobial resistant bacteria.…”
Section: Investigation Of Bacterial Drug Resistancementioning
confidence: 99%
“…The presence of antimicrobial resistant bacteria in natural environmental fields poses a great risk to human health. Raman-deuterium labeling has been advertised for investigating the bacterial response to antibiotics in river water [58]. The study revealed that environmental isolates of Pseudomonas veronii and Citrobacter freundii are metabolically active in presence of carbenicillin and kanamycin.…”
Section: Investigation Of Bacterial Drug Resistancementioning
confidence: 99%
See 1 more Smart Citation